2015
DOI: 10.3389/fnbeh.2015.00089
|View full text |Cite
|
Sign up to set email alerts
|

Altered explorative strategies and reactive coping style in the FSL rat model of depression

Abstract: Modeling depression in animals is based on the observation of behaviors interpreted as analog to human symptoms. Typical tests used in experimental depression research are designed to evoke an either-or outcome. It is known that explorative and coping strategies are relevant for depression, however these aspects are generally not considered in animal behavioral testing. Here we investigate the Flinders Sensitive Line (FSL), a rat model of depression, compared to the Sprague-Dawley (SD) rat in three independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 55 publications
1
18
1
Order By: Relevance
“…Still, there were more differences in the present study between trials 1 and 2 than between individuals tested repeatedly with 1 week intertest interval in adolescence (Lundberg et al, 2019). This indicates that the present finding could be more due to developmental effects since the memory effect can be assumed to be stronger with 1 week intertest interval than with 5 weeks, even though the memory effect in adulthood has been described with testing intervals between 1 and 6 weeks (Meyerson et al, 2006;Roman et al, 2007;Karlsson et al, 2009;Roman and Colombo, 2009;Magara et al, 2015).…”
Section: Discussioncontrasting
confidence: 55%
“…Still, there were more differences in the present study between trials 1 and 2 than between individuals tested repeatedly with 1 week intertest interval in adolescence (Lundberg et al, 2019). This indicates that the present finding could be more due to developmental effects since the memory effect can be assumed to be stronger with 1 week intertest interval than with 5 weeks, even though the memory effect in adulthood has been described with testing intervals between 1 and 6 weeks (Meyerson et al, 2006;Roman et al, 2007;Karlsson et al, 2009;Roman and Colombo, 2009;Magara et al, 2015).…”
Section: Discussioncontrasting
confidence: 55%
“…The selectively bred FSL rat strain is extensively used as an animal model for depression, and one of its characteristic behavior is increased sensitivity to stress [ 13 , 18 ]. One neurobiological mechanism associated with its depressed behavior is increased glutamate transmission and reduced plasticity in the hippocampus, conveyed by reduced levels of the glutamate transporter GLAST and reduced levels of D-serine [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other tests that are gaining in popularity are based on natural behaviors, such as social interaction and/or the motivation to explore, rather than examining the response to a given stimulus or stressful situation. For example, our group and others have shown that decreased exploratory behavior is associated with a depression-like phenotype ( Kasahara et al, 2007 ; Li et al, 2010 ; Gómez-Galán et al, 2013 ; Magara et al, 2015 ). Several auxiliary tests can be used to obtain a more complete evaluation of an animal model or the response to a drug; in particular, tests for memory and anxiety are commonly used ( Lapiz-Bluhm et al, 2008 ).…”
Section: What Do We Talk About When We Talk About Depression In Rodenmentioning
confidence: 94%